Implementation of Hybrid Methods in the Application of Experimental Psychology for Analysis of Mental Endurance Conditions - Usman Nurhasan; Anugrah Nur Rahmantyo; Aflah Rahman Maulidiyah (Khazanah Informatika, 2021)
Psychology is the study of the behavior and mental processes of a person. In psychology, psychological tests or psychological tests are often used as part of the selection to determine the maximum performance of prospective employees based on mental endurance conditions from the factors of speed, accuracy, and consistency. One of the psychological test tools is the Mirror Tracer Apparatus which is used to determine the condition of a person's mental endurance with visual coordination in responding to the inverted image of an object seen through a mirror. Because the use of the Mirror Tracer Apparatus only uses one pattern, and the cost is quite expensive, an Experimental Psychology Implementation Application is created which is implemented in an Android-based application to make it easier with many patterns. This application is designed using a combination of two methods (Hybrid Method). The Fuzzy Mamdani method is used to generate a mental health condition level score, and the Template Matching method is to match the pattern of the resulting images with the template. These two methods aim to apply the psychological knowledge base to the application. Data processing is carried out by giving weight ratings to the experimental tools carried out by the user. The results of this study have been tested on psychologists, resulting in a score of 83% agreeing that the application can be used as an alternative test tool, and 92% of prospective new employees stated that the application can determine the condition of mental endurance.